IMPRESSIONS MAGAGEMENT STUDY WITH EMPLOYEES AT AN OPTICAL SHOP - dos Santos Ferreira, Camilly; Eduarda Melo de Souza, Jhamily; Francisco Campos Pianno, Rafael (Revista Interface Tecnológica, 2024)
Impression management in organizations is extremely intertwined with our daily lives, being a way for companies to control the behavior of their employees to provide to convey a certain image, and especially when the individual shapes their own image and profile to control the impression of the another about your own image. This work aims to identify impression management strategies with employees from a traditional perspective located in the city of Catanduva-SP. A survey was carried out through the application of a questionnaire with the company's eight employees so that their most common behaviors are understood used in the work environment with the purpose of knowing which of the five impression management strategies are the most used. The study provided optical store owners with insights into how employees manage their impressions. The results of the most commonly used strategies are in the following order: insinuation, self-promotion, example-making, supplication, and finally, intimidation.